Aesthetics of the Cowongan Dance at Sanggar Sekar Shanty Banjarnegara - Dian Wardani Putri; Muhammad Jazuli (Gondang: Jurnal Seni dan Budaya, 2025)
This research aims to analyze the aesthetics in the Cowongan Dance by Gading Nadaswara Kemilau Banyu Biru. Cowongan dance has its own uniqueness and specifically has never been studied regarding its aesthetics so researchers are interested in conducting research. This research uses a qualitative descriptive approach with data collection techniques, namely observation, in-depth interviews and document review. The analysis was carried out using aesthetic theory which includes form, weight or content, and appearance. The results of this research show that aesthetics seen from the form side, the Cowongan Dance has a unique form of presentation with ritual-themed choreography as a development of creative dance works. Judging from its weight, the Cowongan Dance contains a magical atmosphere and a message of preserving the traditions of the local community. In terms of appearance, this dance is presented with dynamic choreography supported by movements, unique props, make-up and clothing, as well as musical accompaniment that strengthens the meaning of the Cowongan Dance. This research reveals the aesthetic values ​​created from local community traditions through the creativity of the younger generation to preserve them.